Towards a lumped approach for solid plastic waste gasification: Polyethylene and polypropylene pyrolysis. (1st February 2023) - Locaspi, Andrea; Pelucchi, Matteo; Mehl, Marco; Faravelli, Tiziano
Graphical abstract: Highlights: Semi-detailed kinetic framework for SPW pyrolysis and gasification. Extension of a validated functional group-based approach to PE and PP pyrolysis. Lumping simplifies the complex chemistry of SPW preserving the physical meaning. Wide range validation of the model at pyrolysis and gasification temperatures. Abstract: In a circular economy perspective, solid plastic wastes (SPW) can become a valuable source of chemicals, energy vectors and fuels through pyrolysis, gasification, and partial oxidation technologies, but their modelling requires first the definition of suitable condensed phase pyrolysis mechanisms for each constituent. This work proposes a semi-detailed kinetic model for polyethylene (PE) and polypropylene (PP) pyrolysis based on the functional group approach implemented for polyvinylchloride (PVC) and biomass pyrolysis to consistently address mixture modelling. This approach distinguishes polymeric chains in High Molecular Weight species, represented through their chemical functionalities, and Low Molecular Weight species, described with accuracy comparable to literature detailed models, employing the reaction classes proposed in the scientific literature. Several validated lumping techniques are introduced to reduce the model computational cost, and the resulting liquid-phase model accounts for 74 species for PE and 126 species for PP. Model validation is carried out by an extensive comparison with experimental data proving the soundness of the approach and the model capability of predicting mass-loss and product distribution profiles with similar accuracy to more expensive detailed models from the literature. The proposed condensed phase approach can be extended to other polymers and coupled with other existing subsets in the CRECK kinetic framework (e.g., biomass, PVC) paving the way for unravelling mixture interactions and secondary cracking and/or gasification reactions. The model here proposed is a powerful tool to support design and optimization of SPW thermochemical recycling technologies.